Double Less Sdn Bhd / Sharifah Husnul Hasanah Syed Sharapudin ... [et.al] - Sharifah Husnul Hasanah, Syed Sharapudin; Nurul Fahimah, Abdul Malik; Fara Zarith, Ruzalan; Mohd Irwan, Ibrahim; Narita, Khailani (Faculty of Communication and Media Studies, 2004)
The rapid improvement in trendy and sporty clothes for adults and teenagers encouraged us to form a business in retail shop. We are only interest in making this business because it easy to set up. Also , we believe that it will have a big potential to grow wider and gain a lot of profit. All this factors have influenced our choice of business. Double Less Sdn Bhd is a trading company that sales reject stuff from three brands, Adidas, Levi's and Converse. We named our company as Double Less because merchandise is sales chipper then the proper stuff. We choose to provide this type of business because we found that there is a lots of opportunity to gain profits. We are not worried about the competitors, because presently there are - competitors that running the similar business. We have a potential to grow bigger. The sale of our business is expected to increase in every year. We pretty sure that our business can survive longer and making more profits and produce a good services and products.